2005
DOI: 10.1055/s-2005-837822
|View full text |Cite
|
Sign up to set email alerts
|

Indole Alkaloids of a Thai Medicinal Herb,Mitragyna speciosa,that has Opioid Agonistic Effect in Guinea-Pig Ileum

Abstract: Recently, we found that mitragynine, a major constituent of Mitragyna speciosa, has an opioid agonistic activity, but its weak potency could not explain the opium-like effect of this plant. In the present study, bioassay-guided fractionation of the crude extract of the leaves of M. speciosa was carried out to search for potent opioid agonists other than mitragynine. Opioid agonistic activities were evaluated using twitch contraction induced by electrical stimulation in guinea-pig ileum. The crude extract of M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…This medicinal herb contains many indole alkaloids (Takayama, 2004). (E)-Methyl 2- ((2S,3S,7aS,12bS)-3-ethyl-7a-hydroxy-8-methoxy-1,2,3,4,6,7,7a,12b-octahydroindolo[2,3-a]quinolizin-2-yl)-3-methoxyacrylate (7-hydroxymitragynine), a main active constituent of this plant, is an indole alkaloid that is structurally different from morphine (Horie et al, 2005). We have reported that 7-hydroxymitragynine induces a potent antinociceptive effect on mouse acute pain through the activation of m-opioid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…This medicinal herb contains many indole alkaloids (Takayama, 2004). (E)-Methyl 2- ((2S,3S,7aS,12bS)-3-ethyl-7a-hydroxy-8-methoxy-1,2,3,4,6,7,7a,12b-octahydroindolo[2,3-a]quinolizin-2-yl)-3-methoxyacrylate (7-hydroxymitragynine), a main active constituent of this plant, is an indole alkaloid that is structurally different from morphine (Horie et al, 2005). We have reported that 7-hydroxymitragynine induces a potent antinociceptive effect on mouse acute pain through the activation of m-opioid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…We have found multiple packaged commercial Kratom products to contain artificially elevated concentrations of 7-hydroxymitragynine, the alkaloid responsible for M. speciosa's concerning mechanistic and side effect profile [20][21][22]. The amount of 7-hydroxymitragynine exceeded that found in naturally occurring material by up to 500 %.…”
Section: Resultsmentioning
confidence: 99%
“…Accounting for roughly 2 % of the plant's alkaloid content [16], 7-hydroxymitragynine is an opioid receptor agonist (like mitragynine) but demonstrates potent mu and kappa receptor selectivity [12]. This alkaloid is the major contributing factor for Kratom's analgesic properties, demonstrating opioid receptor affinity up to 17 times that of morphine [20][21][22]. It may also contribute to problematic Kratom use, which has been reported numerous times in the literature [10,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The crude base fraction was found to also inhibit twitch contraction. 24,25) To clarify the active principle in the alkaloidal fraction, the crude base was separated by column chromatography as mentioned above (Section 2.1) to give five alkaloids including one new compound. Initially, several pharmacological evaluations of the major alkaloid, mitragynine (1), were performed to give the following significant results.…”
Section: )mentioning
confidence: 99%